Analisis persepsi Generasi Z terhadap pembelian pakaian bekas pada sosial media di Indonesia - Julia, Sefira Rachma; Zunaedi, Rizqa Amelia; Putra, Perdana Suteja (Journal of Management and Digital Business, 2024)
The development of fashion trends in Indonesia is experiencing rapid growth; one of the growing trends in the fashion industry today is "Thrifting." Thrifting is an activity of shopping for used clothing that is still suitable for use to help reduce textile waste, increase environmental awareness, and create a unique fashion style. This study aims to determine what factors influence Generation Z's intention to purchase secondhand clothing on social media in Indonesia. The sampling technique in this study was purposive sampling, and the sample size was 200 respondents. The data collection technique was done by distributing questionnaires online to Generation Z living in Indonesia. The results of this study indicate that Social Environmental Awareness, Need for Uniqueness, and Brand Awareness have an influence on the Intention to Buy Secondhand Clothing influencing Purchase Behavior. Meanwhile, preconceptions about secondhand clothing and social prestige do not influence the intention to buy secondhand clothing.